2011
DOI: 10.5384/sjovs.vol4i2p6-13
|View full text |Cite
|
Sign up to set email alerts
|

Coloured filters will not give red-green colour deficient observers normal colour vision

Abstract: There have been several reports over the last 200 years on how coloured filters might improve red-green colour deficient observers’ ability to discriminate colours. Many red-green colour deficient observers have unrealistic expectations with regards to the effect of such filters after reading some of these accounts. This case report presents the accounts of three young men with red-green colour-deficiency who share an ambition to study for a profession that require normal trichromatic colour vision: shipmast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…It has previously been suggested that the loss of chromatic signal in anomalous trichromats due to reduced separation of the cone spectral sensitivities might be ameliorated by the use of selective filters that would act to increase their spectral separation [46,47]. The MLDS paradigm for measuring contrast appearance would be an ideal paradigm for studying the long-term effects of such aids on contrast perception.…”
Section: Implications For Compensationmentioning
confidence: 99%
“…It has previously been suggested that the loss of chromatic signal in anomalous trichromats due to reduced separation of the cone spectral sensitivities might be ameliorated by the use of selective filters that would act to increase their spectral separation [46,47]. The MLDS paradigm for measuring contrast appearance would be an ideal paradigm for studying the long-term effects of such aids on contrast perception.…”
Section: Implications For Compensationmentioning
confidence: 99%